Development of Audiovisual Learning Media Using Interactive Powerpoint to Improve Student Activity and Learning Outcomes in Grade X Economics Classes - Indah Damayanti; Sukirno Sukirno (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to develop interactive PowerPoint-based audio-visual learning media for Grade X Economics and to test its feasibility and effectiveness in improving student activity and learning outcomes. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of students in grades X6 and X7 at SMA N 1 Ngluar and SMA Muhammadiyah 1 Muntilan. Data were collected through interviews, questionnaires, and learning outcome tests. The feasibility test results showed that the interactive PowerPoint media was considered very feasible to use, with an average score of 4.6 from subject matter experts, 4.8 from media experts, 4.45 from teachers, and 4.5 from students. The effectiveness test showed N-Gain Scores for activity and learning outcomes of 0.42 and 0.58, respectively, at SMA N 1 Ngluar and 0.44 and 0.55 at SMA Muhammadiyah 1 Muntilan. Thus, interactive PowerPoint media is effective in increasing student activity and learning outcomes in economics learning.